Psychopharmacoepidemiology of antidepressant medications among homeless and unstably housed service users in the Veterans Affairs healthcare system. (19th November 2021) - Tsai, Jack; Szymkowiak, Dorota; Iheanacho, Theddeus
Abstract: Objective: This study conducted a pharmacoepidemiologic examination of antidepressant prescription patterns in homeless and unstably housed (HUH) populations. Methods: Data were analyzed on over 2.6 million veterans from the U.S. Department of Veterans Affairs (VA), the largest provider of healthcare for HUH veterans and a system that does not require healthcare insurance. Results: Multivariable analyses revealed that HUH veterans with depression and PTSD were less likely to receive an antidepressant Rx compared to their stably housed (SH) counterparts with these conditions (OR = 0.77, 99% CI = 0.74–0.79; and OR = 0.87, 99% CI = 0.84–0.90, respectively). Antidepressants were mostly prescribed in specialty mental health care settings, but HUH veterans were less likely to be prescribed antidepressants in primary care settings than SH veterans. In the total sample, the 40–49 age group, female sex, VA service‐connected disability,  outpatient mental health visits, and emergency department visits were positively associated with any antidepressant Rx. Nearly all psychiatric diagnoses were more associated with prescription of selective serotonin reuptake inhibitors/serotonin and norepinephrine reuptake inhibitors (SSRIs/SNRIs) than tricyclic antidepressants. Conclusion: These findings highlight socioeconomic disparities in antidepressant Rx in a healthcare system that does not rely on insurance and suggest clinical challenges with antidepressant prescriptions in HUH populations.